Characterization of Streptococcus pyogenes Strains from Tonsillopharyngitis and Scarlet Fever Resurgence, 2023—FIRST Detection of M1UK in Bulgaria - Emma Keuleyan; Theodor Todorov; Deyan Donchev; Ani Kevorkyan; Radoslava Vazharova; Alexander Kukov; Georgi Todorov; Boriana Georgieva; Iskra Altankova; Yordanka Uzunova (Microorganisms)
Recently a resurgence of Streptococcus pyogenes infections has arisen, with concerns around the highly virulent M1UK lineage. Our aim was to characterize S. pyogenes, the immune responses it causes, and to determine the presence of the M1UK lineage in Sofia, Bulgaria. In our study, the infections were confirmed by culture testing or rapid antigen test. Identification was performed by MALDI-TOF and was followed up by antibiotic susceptibility testing (EUCAST). Virulence factors were identified using multiplex PCR and whole genome sequencing (WGS). Immune responses were measured through detection of serum complement levels, lymphocyte subsets, and cytokine profiling. Out of 82 children, 38 had scarlet fever and the rest had streptococcal pharyngitis. Strains were susceptible to penicillin (β-lactams), macrolides, clindamycin, tetracyclines, co-trimoxazole, fluoroquinolones, and linezolid. Superantigen profiles were identified: SpeA + SpeJ (45%), SpeC, and SpeI + SpeH (27.5% each). A novel Multilocus sequence typing (MLST) haplotype in the mutS gene (d90b) was found in four strains. The M1UK lineage was detected for the first time in Bulgaria. We observed an increase in complement fractions C3 and C4 and a decrease in T lymphocytes. A significant increase in the levels of IFN-γ, IL-6, and IL-10 with corresponding reduction in IL-17A were revealed. In conclusion, the studied S. pyogenes strains were characterized by their susceptibility to antibiotics and the predominance of SpeA superantigen; for the first time in Bulgaria the presence of M1UK and a novel SNP variation in the mutS gene (d90b) were found. A mixed pattern of pro- and anti-inflammatory immune responses in patients was observed.